EFFECT OF EXTRACT GEL GREEN TEA (Camelia Sinensis) ON NEUTROPHIL OF POST EXTRACORONAL BLEACHING RAT’S TEETH - Kristanti, Yulita; Handajani, Juni; Untara, Tri Endra; Santosa, Pribadi (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: Free radicals produced by hydrogen peroxide after teeth bleaching which diffuse through the enamel and dentinal tubules can trigger inflammation of the pulp. To overcome this negative side effect, exogenous antioxidants have been proposed. This research was conducted to determine the effect of natural antioxidants, namely 5% and 10% green tea, which was applied on rat molars teeth that were bleached using 40% hydrogen peroxide. Methods: Fifteen molar teeth of male Wistar rats were bleached using 40% hydrogen peroxide on their occlusal surface. Furthermore, the control group (Group I) rinsed using warm distilled water, while in Group II and Group III, the teeth were rinsed using 5% and 10% green tea extract gel. Wistar rats were sacrificed on the fifth day after treatment, followed by hematoxylin-eosin staining. Histological examinations were observed under a light microscope using 400x magnification and the number of the neutrophil were counted. Result: One-way ANOVA test showed that there was a significant effect of green tea extract gel concentration on the number of neutrophils (p 0.05). Post hoc test results showed that there were significant differences in all pairs of groups compared (p 0.05). Conclusion: Group III which was treated using10% green tea extract gel has the lowest number of neutrophil compared to Group II which was treated using 5% green tea extract hel and the control group.